2022
DOI: 10.3390/antiox11030571
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Selenoprotein T Mimetic, PSELT, Induces Preconditioning-like Myocardial Protection by Relieving Endoplasmic-Reticulum Stress

Abstract: Oxidative stress and endoplasmic reticulum stress (ERS) are strictly involved in myocardial ischemia/reperfusion (MI/R). Selenoprotein T (SELENOT), a vital thioredoxin-like selenoprotein, is crucial for ER homeostasis and cardiomyocyte differentiation and protection, likely acting as a redox-sensing protein during MI/R. Here, we designed a small peptide (PSELT), encompassing the redox site of SELENOT, and investigated whether its pre-conditioning cardioprotective effect resulted from modulating ERS during I/R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…SELENOT is strongly expressed in human and mouse pancreatic β- and δ-cells, and conditional pancreatic β-cell SELENOT-knockout mice exhibited impaired glucose tolerance with a deficit in insulin production/secretion [ 14 ]. On the other hand, SELENOT is highly expressed during the early hyperplastic growth of cardiomyocytes, suggesting its involvement in cardiac development during embryogenesis, and can also protect cardiomyocytes following myocardial ischemia/reperfusion (MI/R) insult [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…SELENOT is strongly expressed in human and mouse pancreatic β- and δ-cells, and conditional pancreatic β-cell SELENOT-knockout mice exhibited impaired glucose tolerance with a deficit in insulin production/secretion [ 14 ]. On the other hand, SELENOT is highly expressed during the early hyperplastic growth of cardiomyocytes, suggesting its involvement in cardiac development during embryogenesis, and can also protect cardiomyocytes following myocardial ischemia/reperfusion (MI/R) insult [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent ones have recently reported the use of selenoprotein-derived peptides with promising results in brain disorders. The selenopeptide, PSELT, composed of 10 amino acids with a Sec redox center, is protective in a rat model of peripheral nerve neurodegeneration and a MPTP mouse model of PD, but also in a rat model of cardiac ischemia-reperfusion [ 93 , [178] , [179] , [180] ]. Transcriptomic analysis revealed that gene regulation by PSELT after MPP + treatment of neuroblastoma cells is positively correlated with that after resveratrol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…H9c2 cardiomyocytes were purchased from the American Type Culture Collection (ATCC) (Manassas, VA, USA) (Cat# CRL -1446) and cultured as described in our previous publications [ 27 , 28 , 29 , 30 ]. When cell confluence reached 80%, H9c2 cardiomyocytes were digested in a 1:2 ratio with 0.25% trypsin-EDTA (1X) (Gibco), according to the manufacturer’s instructions (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…When cell confluence reached 80%, H9c2 cardiomyocytes were digested in a 1:2 ratio with 0.25% trypsin-EDTA (1X) (Gibco), according to the manufacturer’s instructions (ATCC). For all experiments, H9c2 cells were plated in complete medium and incubated at 37 °C and 5% CO 2 for 48 h, as previously reported [ 27 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation